Application of Cooperative Learning Type of Student Team Achievement Divisions in Fiqh Subjects at MIMA 42 Wuluhan - Syamsi Rega Virgi Wulandari; Jasuli Jasuli; Abdul Karim (EDUCARE: Journal of Primary Education, 2022)
Learning is a process of interaction that occurs between teachers and students. The learning process requires a way or method so that interaction occurs reciprocally and can achieve the desired learning goals. This research uses a descriptive qualitative approach, and the type of research is a case study. Data collection techniques using observation, interviews, and documentation. While the data analysis with an interactive analysis model (interactive analysis)—the validity of this research data uses the triangulation technique. The results of this study indicate (1) Planning for STAD Type Cooperative Learning Methods in Fiqh Subjects at MIMA 42 Wuluhan, namely: The teacher makes a Learning Implementation Plan (RPP), makes observation sheets and score assessment sheets, choose learning media, makes materials and questions. group and individual assignments, and designing study groups. (2) Implementation of STAD Type Cooperative Learning Method in Fiqh Subjects at MIMA 42 Wuluhan: Initial activity: the teacher explains the material that will be given to students. The core activities are: The teacher explains the method to be used, divides students into several groups, plays videos as material, asks students to observe pictures/videos of people, and discusses the material in the video. And all groups present the results of their discussions. Closing activities, namely: providing reinforcement to the material presented by students, the teacher and students reciting prayers, and the teacher planning follow-up learning. (3) Evaluation of STAD Type Cooperative Learning Method in Class Fiqh Subjects at MIMA 42 Wuluhan Jember, namely: Evaluation of observation and performance (demonstration) on group performance. Meanwhile, individual evaluation is in the form of homework (PR). Pembelajaran adalah proses interaksi yang terjadi antara guru dan peserta didik. Dimana dalam proses pembelajaran membutuhkan cara atau metode agar supaya interakasi terjadi secara timbal balik dan bisa mencapai tujuan pembelajaran yang dinginkan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dan jenis penelitian studi kasus. Tehnik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Sedangkan analisis data dengan model analisis interaktif (interactive analysis). Keabsahan data penelitian ini menggunakan teknik trianggulasi. Hasil penelitian ini menunjukkan: (1) Perencanaan Metode Pembelajaran Kooperatif Tipe STAD Pada Mata Pelajaran Fiqih Di MIMA 42 Wuluhan, yaitu: Guru membuat Rencana Pelaksanaan Pembelajaran (RPP), mebuat lembar observasi dan lembar penilaian skor, memilih media pembelajaran, membuat materi dan soal tugas kelompok dan individu, dan mendesain kelompok belajar. (2) Pelaksanaan Metode Pembelajaran Kooperatif Tipe STAD Pada Mata Pelajaran Fiqih Di MIMA 42 Wuluhan, yaitu: Kegiatan awal: guru menjelaskan materi yang akan di berikan kepada peserta didik. Kegiatan inti yaitu: Guru menjelaskan metode yang akan digunakan, membagi peserta didik dalam beberapa kelompok, memutar video sebagai bahan materi, menyuruh peserta didik untuk mengamati gambar/video orang, siswa mendiskusikan materi yang ada di video. dan semua kelompok memaparkan hasil diskusinya. Kegiatan penutup, yaitu: memberikan penguatan terhadap materi yang disampak oleh sisiwa, Guru bersama peserta didik melafalkan doa dan Guru merencanakan tindak lanjut pembelajaran. (3) Evaluasi Metode Pembelajaran Kooperatif Tipe STAD Pada Mata Pelajaran Fiqih Kelas Di MIMA 42 Wuluhan Jember, yaitu: Evaluasi observasi dan unjuk kerja (demonstrasi) terhadap kinerja kelompok. Sedangkan Evaluasi individu berupa pekerjaan rumah (PR).